Indoximod: An Immunometabolic Adjuvant That Empowers T Cell Activity in Cancer - Fox, Eric; Oliver, Thomas; Rowe, Melissa; Thomas, Sunil; Zakharia, Yousef; Gilman, Paul B.; Muller, Alexander J.; Prendergast, George C. (Frontiers in Oncology, 2018)
Exploding interest in immunometabolism as a source of new cancer therapeutics has been driven in large part by studies of tryptophan catabolism mediated by IDO/TDO enzymes. A chief focus in the field is IDO1, a pro-inflammatory modifier that is widely overexpressed in cancers where it blunts immunosurveillance and enables neovascularization and metastasis. The simple racemic compound 1-methyl-D,L-tryptophan (1MT) is an extensively used probe of IDO/TDO pathways that exerts a variety of complex inhibitory effects. The L isomer of 1MT is a weak substrate for IDO1 and is ascribed the weak inhibitory activity of the racemate on the enzyme. In contrast, the D isomer neither binds nor inhibits the purified IDO1 enzyme. However, clinical development focused on D-1MT (now termed indoximod) due to preclinical cues of its greater anticancer activity and its distinct mechanisms of action. In contrast to direct enzymatic inhibitors of IDO1, indoximod acts downstream on mTORC1, a convergent effector signaling molecule for all IDO/TDO enzymes, thus possibly lowering risks of drug resistance by IDO1 bypass. In this review, we survey the unique biological and mechanistic features of indoximod as an IDO/TDO pathway inhibitor, including recent clinical findings of its ability to safely enhance various types of cancer therapy, including chemotherapy, chemo-radiotherapy, vaccines and immune checkpoint therapy. We also review the potential advantages indoximod offers compared to selective IDO1-specific blockade, which preclinical studies and the clinical study ECHO-301 suggest may be bypassed readily by tumors. Indoximod lies at a leading edge of broad-spectrum immunometabolic agents that may act to improve responses to many anticancer modalities, in a manner analogous to vaccine adjuvants that act to boost immunity in settings of infectious disease.